The Influence Of Capital Structure And Corporate Social Responsibility On Firm Value With Sharia Compliance As A Moderating Variable - Asri; Syaakir Sofyan; Irham Pakkawaru (Journal of Contemporary Economics and Business Management, 2026)
The development of the Islamic capital market in Indonesia encourages companies to not only enhance financial performance but also pay closer attention to social responsibility and Sharia compliance. Firm value serves as a critical indicator reflecting investor confidence. However, prior empirical findings regarding the effects of capital structure and corporate social responsibility (CSR) on firm value remain inconsistent. This study aims to analyze the influence of capital structure and CSR on firm value, with Sharia compliance acting as a moderating variable, focusing on companies listed in the Jakarta Islamic Index (JII) during the 2022–2024 period. Employing a quantitative approach, this research utilizes secondary data sourced from corporate annual reports and financial statements. A sample of 14 companies was selected via purposive sampling, yielding a total of 42 observations. Data analysis was executed using multiple linear regression and Moderated Regression Analysis (MRA) processed through EViews 12. The empirical results demonstrate that capital structure has no significant effect on firm value (p = 0.2612 > 0.05). Conversely, CSR exerts a significant negative effect on firm value (p = 0.0003 < 0.05), while Sharia compliance exhibits a significant positive effect (p = 0.0005 < 0.05). Simultaneously, all variables significantly influence firm value, with a Prob(F-statistic) of 0.000000 < 0.05. The Adjusted R-squared value of 0.861670 indicates that the explanatory variables account for 86.16% of the variance in firm value. Furthermore, the moderation analysis confirms that Sharia compliance significantly moderates the relationship between both capital structure and CSR on firm value.